Lipidome alterations in human prefrontal cortex during development, aging, and cognitive disorders - Yu, Qianhui; He, Zhisong; Zubkov, Dmitry; Huang, Shuyun; Kurochkin, Ilia; Yang, Xiaode; Halene, Tobias; Willmitzer, Lothar; Giavalisco, Patrick; Akbarian, Schahram; Khaitovich, Philipp (Molecular psychiatry, 2020)
Lipids are essential to brain functions, yet they remain largely unexplored. Here we investigated the lipidome composition of prefrontal cortex gray matter in 396 cognitively healthy individuals with ages spanning 100 years, as well as 67 adult individuals diagnosed with autism (ASD), schizophrenia (SZ), and Down syndrome (DS). Of the 5024 detected lipids, 95% showed significant age-dependent concentration differences clustering into four temporal stages, and resulting in a gradual increase in membrane fluidity in individuals ranging from newborn to nonagenarian. Aging affects 14% of the brain lipidome with late-life changes starting predominantly at 50-55 years of age-a period of general metabolic transition. All three diseases alter the brain lipidome composition, leading-among other things-to a concentration decrease in glycerophospholipid metabolism and endocannabinoid signaling pathways. Lipid concentration decreases in SZ were further linked to genetic variants associated with disease, indicating the relevance of the lipidome changes to disease progression.